MENUJU SEKOLAH SEHAT BERBUDAYA LINGKUNGAN SMPN SATU ATAP PULAU PARI KEPULAUAN SERIBU - Faisal M. Jasin; Rihlah Nur Aulia; Haerul Anwar; Alvin Pratya Aryansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2024)
Abstract The purpose of this service is to provide reinforcement in increasing understanding and implementation towards environmentally friendly healthy schools in archipelagic schools. Creating a healthy school environment is the most important thing that must be prepared by educational units, especially in archipelagic schools. A healthy school environment can be used as a fun learning resource for the achievement of optimal learning processes and outcomes, a healthy school with Environmental Culture which is based on awareness and understanding of the current condition of the school environment and the surrounding environment as one of the smallest environmental units, in order to develop creations, tastes, karsa and works to maintain, improve, and improve the quality of the current and future environment, especially in the archipelago. The method used is through socialization to go to a healthy school with environmental culture. The results of the service are first, the principal, teachers are able to understand and be aware of the current environmental conditions. Second, school principals and teachers, staff are able to formulate efforts to maintain, improve, and improve the quality of the environment. Third, school residents care about the environment, and are able to realize their concern for nature and island preservation in daily life, especially the school environment and the surrounding environment as a school in the archipelago as an ecosystem unit. Keywords: school; healthy; cultured environment; archipelago Abstrak Tujuan pengabdian ini untuk memberikan penguatan dalam peningkatan pemahaman dan implementasi menuju sekolah sehat berbidaya lingkungan di sekolah kepulauan. Menciptakan lingkungan sekolah yang sehat merupakan hal terpenting yang harus disiapkan oleh satuan pendidikan terutama di sekolah kepulauan.. Lingkungan sekolah yang sehat dapat dijadikan sebagai sumber belajar yang menyenangkan demi tercapainya proses dan hasil belajar yang optimal, sekolah sehat Berbudaya Lingkungan yang dilandasi oleh kesadaran dan pemahaman atas kondisi lingkungan sekolah dan lingkungan sekitar saat ini sebagai satu unit lingkungan terkecil, dalam rangka mengembangkan cipta, rasa, karsa dan karya untuk memelihara, memperbaiki, dan meningkatkan kualitas lingkungan hidup saat ini dan yang akan datang terutama di kepulauan. Metode yang digunakan adalah melalui sosialisasi untuk menuju sekolah sehat berbudaya lingkungan. Hasil pengabdian adalah : pertama, kepala sekolah, guru Mampu memahami dan sadar terhadap kondisi lingkungan saat ini. Kedua, kepala sekolah dan guru, tendik mampu merumuskan upaya untuk memelihara, memperbaiki, dan meningkatkan kualitas lingkungan. Ketiga, warga sekolah Peduli terhadap lingkungan, dan mampu mewujudkan kepeduliannya tersebut alam dan pelestarian pulau dalam kehidupan sehari-hari Terutama lingkungan sekolah dan lingkungan sekitarnya sebagai sekolah di kepualauan sebagai satu unit ekosistem. Kata Kunci: sekolah; sehat; berbudaya lingkungan; kepulauan